Hubungan Kesadaran dan Pengetahuan Gizi serta Kesadaran Kesehatan terhadap Status Gizi Remaja Jakarta - Miranda Zerlina; Wardina Humayrah (Universitas Baiturrahim, 2023)
Adolescents are prone to nutritional problems due to various factors including: diet, body perception, physical activity, medical conditions, and lifestyle. Adolescent awareness about health and nutrition, as well as knowledge of nutrition could influence that various factors due to nutritional problems in adolescents. This study aimed to analyze the relationship between nutritional awareness, nutritional knowledge, and health awareness on the nutritional status of adolescents. The design of this study was cross-sectional with 98 respondents aged 15-18 years selected by random sampling in SMA Negeri 4 Jakarta. Health awareness data was collected using the Health Conciousness Scale, nutrition awareness using a nutrition awareness questionnaire, and nutrition knowledge using a nutrition knowledge questionnaire. Data were analyzed using the Spearman rank test. The results showed that the majority (> 50%) of the respondents had normal nutritional status with sufficient nutritional knowledge and moderate nutrition and health awareness categories. There is no significant relationship between awareness and knowledge of nutrition and health awareness on the nutritional status of respondents (p>0.05). Nutritional awareness, nutritional knowledge, and health awareness are not direct causative factors that can affect nutritional status, so it is supposed that there are other factors that directly influence nutritional status, such as nutritional intake or health status. Future studies are expected to be completed with data on nutritional intake and health status as the direct causative factors of nutritional status.